Teachers' and Student Teachers' Perceptions of Effective Teaching of Social Studies - Karasneh, Samih (Jordan Journal of Educational Sciences, 2005)
The purpose of this study was to investigate teachers’ and student teachers’ perceptions of the characteristics of effective social studies teaching. Data were collected using a questionnaire designed to give information on the participants’ perceptions of effective teaching of social studies. The sample of the study included 54 student teachers (those who have newly finished their teaching practice) and 172 social studies teachers (with different levels of experience). The data were analysed with SPSS-X computer programme. The means, percentages and standard deviations were used to analyze the various items and the domains of the questionnaire. Also, one sample t-test was used to examine the differences between the participants perceptions. Although some statistically signficant differences (α =0.05) were revealed, the results of the study emphasized that the participants agreed bout the majority of the characteristics of effective social studies teaching. The study concluded that effective social studies teachers should have good relationships with their students. Besides, they should employ various teaching and learning activities for their teaching to be effective.